Handbook of multicultural mental health : assessment and treatment of diverse populations - Paniagua, Freddy A.; Yamada, Ann Marie (Academic Press, 2013)
This handbook discusses the impact of cultural, ethnic, and racial variables for the assessment, diagnosis, treatment, service delivery, and development of skills for working with culturally diverse populations.